Automatic extension of editing rules for program analysis during creation process - Hashimoto, Wakana; Amano, Yo; Takeuchi, Kazuhiro (2022 13th International Congress on Advanced Applied Informatics Winter (IIAI-AAI-Winter), 2022)
This paper focuses on edits of a program that a programming learner is creating. The proposed method in this paper defines EAST (Extended Abstract Syntax tree), an extension of AST (Abstract Syntax Tree), to analyze programs subject to non-compilable edits. EAST adds editing rules to ASTs, and the proposed method automatically creates them from a given set of ASTs. EAST helps define the learner's program editing behavior as editing on a tree structure. The proposals in this paper provide a foundation for future research that will contribute to a more detailed study of improving the learning efficiency of program learners.